A juventude evangélica e a questão do trânsito religioso: demandas, associações e controvérsias em torno dos rumos religiosos no Brasil - Miranda, Hilder Mateus Nascimento de (2024)
The changes in the Brazilian evangelical segment in recent decades are not restricted to the recruitment and transit of believers, but encompass the emergence of new ideas, demands and configurations. These transformations are expressed in the political, cultural, liturgical and doctrinal fields. In view of this, this work intended to problematize the issue of religious transit in Brazil, with an emphasis on the religious mobility of evangelical youth, taking as a starting point the hypothesis that points out as their main motivation the search for flexibility and religious autonomy and/or political preferences. Thus, the objective was to reflect on the changes in the Brazilian evangelical segment, having as a research field Natal/RN, based on the characterization of the profile of evangelical youth who practiced religious transit, delimiting their religious trajectory and seeking to understand their motivations, as well as their social and political perceptions. To carry out this investigation, methodologies such as: bibliographic review and application of a semi-structured questionnaire with evangelical youth accessed through virtual groups of young people on WhatsApp and Facebook, and through interlocutors from the field of study itself, were used. Finally, the hypothesis used acted as an important guiding thread to evaluate the role of evangelical youth in the context of the 2018 and 2022 presidential elections, expressed in the adoption of postures of agreement, accommodation and silent disagreement, which distance themselves from the posture of conflicting disagreement generally associated with youth as agents of change, in the literature and in the media.